Coleridge on Broad Stand - Vardy, Alan (Romanticism and Victorianism on the Net, 2012)
This essay explores the relationships between Coleridge’s notebook entries and letters to Sara Hutchinson during his tour of the Cumbrian mountains in August 1802, focusing on his nearly disastrous descent from the summit of Scafell. It also revisits his controversial claim that he took those experiences and “transferred” himself “in Spirit” to the Alps in the process of composing “Hymn Before Sun-rise, in the Vale of Chamouny.” The question of how such experiences are “transferrable” has exercised critics from the beginning of Coleridge studies, and the essay offers a new approach by concentrating on the experiential content of the tour as the material of poetic composition.